1999
DOI: 10.1074/jbc.274.48.34450
|View full text |Cite
|
Sign up to set email alerts
|

High Level Calcineurin Activity Predisposes Neuronal Cells to Apoptosis

Abstract: Calcineurin is a Ca2؉ /calmodulin-dependent protein phosphatase that is abundantly expressed in several specific areas of the brain, which are exceptionally vulnerable to stroke, epilepsy, and neurodegenerative diseases. In this study, we assessed the effects of high level activity of calcineurin on neuronal cells. Virus-mediated high level constitutive activity of calcineurin rendered neuronal cells susceptible to apoptosis induced by serum reduction or by a brief exposure to calcium ionophore. Adenovirus-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 54 publications
1
114
1
Order By: Relevance
“…Dephosphorylated Bad translocates from the cytosol to the mitochondria where it inhibits antiapoptotic activity of Bcl-2 and Bcl-x L , ultimately, leading to cell death (Desagher and Martinou, 2000, for review). In accordance, was found to decrease apoptosis of cerebellar granule and cortical cultures after exposure to glutamate (Ankarcrona et al, 1996;Asai et al, 1999) or to amyloidogenic peptides (Agostinho and Oliveira, 2003). FK506 also prevented calcineurin-mediated dephosphorylation of nitric oxide synthase, leading to neuroprotection (Dawson et al, 1993;Nishino et al, 1996).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Dephosphorylated Bad translocates from the cytosol to the mitochondria where it inhibits antiapoptotic activity of Bcl-2 and Bcl-x L , ultimately, leading to cell death (Desagher and Martinou, 2000, for review). In accordance, was found to decrease apoptosis of cerebellar granule and cortical cultures after exposure to glutamate (Ankarcrona et al, 1996;Asai et al, 1999) or to amyloidogenic peptides (Agostinho and Oliveira, 2003). FK506 also prevented calcineurin-mediated dephosphorylation of nitric oxide synthase, leading to neuroprotection (Dawson et al, 1993;Nishino et al, 1996).…”
Section: Introductionmentioning
confidence: 54%
“…This calcium-dependent phosphatase has been described to be involved in many pathways that ultimately lead to cell death (Asai et al, 1999;Springer et al, 2000). Accordingly, inhibition of calcineurin as a relevant event in FK506-mediated protective effects has been demonstrated by many authors (Ankarcrona et al, 1996;Asai et al, 1999;Mobley and Agrawal, 2003;Nishino et al, 1996;Stevens et al, 2003). However, numerous other studies have excluded a substantial contribution of inhibited calcineurin for neuroprotection exerted by FK506 (Sabatini et al, 1997;Snyder et al, 1998;Toung et al, 1999;Yardin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragments of fodrin (120-150 kDa) are generated by caspase and calpain activation during apoptotic cell death (Moore et al, 2002). Ca 2+ /calmodulin-dependent protein phosphatases, such as calcineurin (Asai et al, 1999), also regulate the phosphorylation of LDH, which is dephosphorylated upon MAG cross-linking. Changes in the phosphorylation of LDH have important implications for the control of cell metabolism (Yasykova et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It also plays a role in brain ischemia [3,29] and neural cell apoptosis [1]. Furthermore, recent reports have suggested that calcineurin is involved in the pathogenesis of schizophrenia because conditional calcineurin knockout mice exhibit multiple abnormal behaviors related to schizophrenia [17].…”
Section: Discussionmentioning
confidence: 99%